Peran Keuangan Perilaku dalam Keputusan Investasi dan Pendanaan Berkelanjutan: Tinjauan Sistematis - Chairun Amallia; Dwi Fuji Wahyuni; Fanny Wulanda; Liza Zulbahri (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The development of sustainable finance and digital financial technology has transformed investment and financing decision-making behavior in modern financial markets. Traditional financial theory assumes that investors act rationally; however, behavioral finance explains that financial decisions are also influenced by psychological, emotional, and social factors. This study aims to analyze the role of behavioral finance in investment and sustainable financing decisions through a Systematic Literature Review (SLR) approach. The study adopts the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to identify, screen, and evaluate relevant articles indexed in Scopus and SINTA. A total of 22 selected articles were analyzed descriptively and thematically. The findings indicate that behavioral biases, financial literacy, investor sentiment, risk perception, personality traits, digital finance, ESG awareness, and artificial intelligence significantly influence investment and financing decisions. In addition, the integration of financial technology, machine learning, and sustainable finance has become an emerging trend in modern behavioral finance research. The study also reveals that previous studies remain fragmented and have not comprehensively integrated behavioral finance, sustainable finance, ESG investment, and digital finance into a unified conceptual framework. This study contributes theoretically to the development of behavioral finance and sustainable finance literature and provides practical implications for investors, companies, academics, and policymakers in understanding financial decision-making behavior in the era of sustainability and digital transformation.